Utilizing digital technologies to promote well-being in university students: the ‘DigiWell’ research protocol - Ruini, Chiara; Vescovelli, Francesca; Cesarano, Valentina Paola; De Angelis, Grazia; De Marco, Erika; De Marco, Elisabetta Lucia; Galeazzi, Gian Maria; Pira, Giorgio Li; Pingani, Luca; Limone, Pierpaolo (Frontiers in Psychology, 2024)
The COVID-19 pandemic has significantly impacted the well-being of university students, particularly those in healthcare and medical programs. Psychological interventions rooted in positive psychology have proven effective in enhancing mental health, with online and digital delivery methods proving to be equally viable. This study aims to enhance mental health among Italian university students through digital interventions, including virtual reality, utilizing a stepped care approach. Specific objectives include implementing online positive interventions for students experiencing mild distress (DigiWell_Step 1), evaluating a Virtual-Reality intervention for moderate distress (DigiWell_Step 2), and identifying students experiencing high distress or optimal well-being. Cluster analyses and linear models will assess intervention outcomes. It is anticipated that students undergoing these steps will experience significant improvements in well-being and distress reduction, with sustained benefits at a three-month follow-up. This research contributes to understanding the efficacy of mental health interventions for university students, leveraging digital technologies to enhance accessibility and user engagement. The integration of digital technologies enhances the cost-effectiveness and engagement of interventions delivered through a stepped care approach tailored to the targeted population.